Increasing incidence of hypertrophic pyloric stenosis. - Tam, P K (1991)
The incidence of pyloric stenosis in the Mersey region rose from 1.54/1000 births in 1976-8 to 2.22/1000 births in 1986-8. Reliance on ultrasonography for diagnosis in the 1980s resulted in fewer 'tumours' being felt; diagnostic delay was not shortened overall but serial ultrasonography showed evolving lesions in six patients. Clinical examination and selective use of ultrasonography is advocated.